NILAI-NILAI KEPAHLAWANAN TOKOH I GUSTI KETUT JELANTIK DALAM PERANG JAGARAGA (1846-1849) SEBAGAI SUMBER PENANAMAN KARAKTER DALAM PEMBELAJARAN IPS DI SMP LABORATORIUM UNDIKSHA SINGARAJA - Wusantria, putu (LPPM Undiksha, 2017)
This research aimed to 1) know the biography of I Gusti Ketut Jelantik in Jagaraga?s War; (2) analyze the character value of I Gusti Ketut Jelantik?s heroism in Jagaraga?s War; (3) analyze the integration of I Gusti Ketut Jelantik?s heroism value as a source of character building in IPS study in SMP Laboratorium Undiksha Singaraja. This research used qualitative research method with: the location of this research is in monument of Jagaraga?s war, Puri Kanginan Buleleng, SMP Laboratorium Undiksha Singaraja, Puri Agung Karangasem, and LVRI Bali; the method to determine an informant is use purposive sampling; the data was collected by observation, interview, and document study; the instrument is use the line of interview to collect the data with camera, audio recorder, and manual recording as a support; the method the to examine the real data is us three methods: theory triangulation or source data, method triangulation, and theory triangulation; the analysis method in this research is use data reduction, data presentation, and drag the conclusion or verification. The result from this research shows the biography of I Gusti Ketut Jelantik or more famous with Patih Jelantik who become the ?Patih Jelantik? in Buleleng Kingdom who also dead in Jagaraga?s war in 1849. The values from I Gusti Ketut Jelantik are: religious, honest, tolerant, hard worker, creative, love the nation, kindly, merciful, and responsible. The integration from the values of I Gusti Ketut Jelantik heroism are made by adding the value of him into the indicator in IPS syllabus, and integrated it in RPP and study lesson.